Glut4 translocation augmentation effects of medicinal plants traditionally used for the management of type II diabetes mellitus - Beseni, Brian Kudakwashe (My University, 2017)
Diabetes mellitus is a chronic metabolic disorder characterised by perpetual hyperglycaemia. Various oral pharmacological theraputic management strategies currently exist but are too expensive and having a host of undesirable side effects. Therefore people resort to the use of traditional medicinal plants as they offer a cost effective and readily available health care avenue. Despite the wide-spread use of traditional medicinal plants, several worrisome concerns about their effectiveness, clinical modes of action and safety have been raised. Leaves of five selected plants (Toona celliata, Seriphium plumosum, Schkuhria pinnata, Olea africana, Opuntia ficus-indica) were collected from Mankweng area, Capricon Local Municipality, Limpopo province, South Africa. Ground plant materials were exhaustively extracted by maceration in methanol, acetone or hexane. The presence of different plant secondary metabolites in the crude extracts was determined using various standard chemical tests and thin layer chromatography (TLC). A myriad of compounds which represented various secondary plant metabolites groups were observed on the TLC plates and were best resolved in the non-polar (BEA) and intermediate (CEF) mobile phases. The total phenolic content and total flavonoids of the different extracts were determined spectrophotometrically using the Folin-Ciocalteu`s phenol reagent method and Aluminium chloride colorimetric assay respectively. The plants contained comparatively higher amounts of total phenolic compounds as compared to the flavonoids. The antiglycation activity of the plant extracts were determined using the bovine serum albumin assay. The acetone extract of Seriphium plumosum (SPlA) exhibited the most glycation inhibitory activity among all the examined extracts, as it resulted in 2,22% glycation. The antioxidant potential of each of the different extracts was quantitatively determined spectrophotometrically using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and the ferric ion reducing power assay. The methanol extract of Seriphium plumosum showed the best antioxidant activity among all the extracts in this study. It exhibited the lowest EC50 values of 0.72 mg/ml and 2.31 mg/ml for the DPPH scavenging activity and the ferric reducing power assay respectively. The cytotoxicity profiles of the different plant extracts on C2C12 cell line were determined using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium xiii bromide (MTT) assay. It was concluded that since the all the extracts investigated had CC50 values greater than 50 μg/ml they were generally non-toxic. The amount of glucose taken up by differentiated C2C12 cells was quantified using the glucose uptake assay. Treatment of the C2C12 cells with the hexane extract of Seriphium plumosum resulted in the best glucose utilisation effect of 35,77% which was higher than that of insulin which was 26,06% after 6 hours. The translocation assay was used to determine the effect of the plant extract on GLUT4 translocation while the expression of various mitogen activated protein kinases in the cells was determined using the human MAPK profiler assay. It was established that treatment with Seriphium plumosum hexane extract resulted in increased GLUT4 translocation from the intracellular vesicular stores to the cell surface membrane. The increase in GLUT4 translocation may have resulted from the upregulation of expression of phosphorylated Akt-1, Akt-2, GSK3β, ERK1, ERK2 p70S kinase and MKK3 under the influence of Seriphium plumosum hexane extract. The study documents a probable insulin-mimetic activity of the hexane extract of Seriphium plumosum. This activity may be responsible for its hypoglycaemic capability and may occur via the augmentation of proximal mitogen activated protein kinases involved in the GLUT4 translocation pathway. Further investigations need to be conducted to ascertain this novel finding which may help provide a cost-effective and readily available antidiabetic therapeutic agent.
Thesis (M. Sc. (Biochemistry)) --University of Limpopo, 2017
Keywords: Glut4; Effects of traditional medicinal plants; Type 11 diabetes mellitus; Blood glucose; Traditional medicine -- South Africa; Diabetes; Medicinal plants -- Biotechnology; Type 2 diabetes